Pesticides and Integrated Crop Management food products: Factors affecting their acceptance by consumers - Simoglou, Konstantinos; Roditakis, Emmanouil (ENTOMOLOGIA HELLENICA, 2023)
The forthcoming changes in the Common Agricultural Policy of the EU are expected to accrue changes to agricultural food products, in terms of pesticide use and food certification. Knowledge of the factors that affect consumer perceptions of certified Integrated Crop Management (ICM) food is imperative to making targeted interventions or taking corrective actions in the future. For this purpose, in the spring of 2021, a survey was conducted in Greece with 1,846 participants. Exploratory factor analysis was applied to the questionnaire variables, followed by binomial logistic regression analysis regarding the research question: If the participants consider that ICM food products are safe or not, in terms of the presence of pesticide residues. Among the participants, the likelihood to express a positive attitude towards the research question was greater among those who trust food certification, those who get informed about pesticides from specialized information sources, who are male, those who positively perceive the contribution of pesticides and finally, the older aged participants (> 45 years old). The results indicate that consumers consider ICM food products to be safe and acceptable in terms of pesticide use issues. Trust in labeling, traceability and certification procedures is the key factor in accepting ICM products. It also appears that specialized information sources on pesticides (bulletins of public bodies, official websites, agronomists, scientific journals) play a key role in shaping consumer views. Measures should be taken by official bodies for targeted consumer information on pesticides and food safety through general information sources and social networks.